Choice, Rights, and Virtue: Prenatal Testing and Styles of Moral Reasoning in Aotearoa/New Zealand. - Fitzgerald, Ruth P.; Legge, Michael; Park, Julie (Medical Anthropology Quarterly, 2015)
Using a Foucauldian biopower analytic, this article combines insights from several ethnographic research projects around the moral reasoning styles underpinning debates over selective reproductive technologies in Aotearoa/New Zealand. We show that divergent or shared public, private, state, individual, and community moral reasoning styles become highly politicized truth discourses that have the potential to, and at times do, affect one another, modifying a dominant, state-supported, principal-based bioethics framework. The styles of moral reasoning that we identify pivot on an aspirational cultural ideal of the provision of choice to citizens, which is taken as an appropriate position from which to regulate selective reproductive technologies.